2019
DOI: 10.1111/jch.13747
|View full text |Cite
|
Sign up to set email alerts
|

Asian management of hypertension: Current status, home blood pressure, and specific concerns in Taiwan

Abstract: Approximately 25% of the population in Taiwan has hypertension, and the rate has increased over time. Although age‐standardized cardiovascular mortality has decreased over the last 25 years, the annual stroke incidence has increased, and national health insurance reimbursement for cardiovascular disease (CVD) has grown by 22% over the last 10 years. Automatic oscillometric sphygmomanometer devices are increasingly available and affordable in Taiwan, making this the main method of out‐of‐office blood pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
0
18
1
2
Order By: Relevance
“…A recent study reported that the prevalence of hypertensive crisis per 1000 visits to the emergency department (ED) has tripled from 1.8 to 4.6 in the United States [ 3 ]. In Taiwan, approximately one in every four Taiwanese has hypertension [ 4 ] and it is estimated that 1–2% of patients with hypertension may develop HTN-C [ 5 ]. Therefore, the management of hypertensive crisis and its associated complications are crucial in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that the prevalence of hypertensive crisis per 1000 visits to the emergency department (ED) has tripled from 1.8 to 4.6 in the United States [ 3 ]. In Taiwan, approximately one in every four Taiwanese has hypertension [ 4 ] and it is estimated that 1–2% of patients with hypertension may develop HTN-C [ 5 ]. Therefore, the management of hypertensive crisis and its associated complications are crucial in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, cardiovascular diseases were the second leading cause of death in 2018 with a mortality rate of 165.8 per 100 000, consisting of a mortality rate of 48.8, 26.1, and 12.8 per 100 000 for heart diseases, cerebrovascular diseases, and hypertension, respectively. 1 Compared with the 2017 statistics, the 2018 cardiovascular mortality rate increased by 4.5%; but decreased by 2.0% in cerebrovascular diseases, and by 1.6% in hypertension.…”
Section: Introductionmentioning
confidence: 94%
“…The prevalence of hypertension in Taiwan has reached a plateau of ∼25% in the general population aged 18 years or over according to the reports of the 2013–15 and 2015–19 Nutrition and Health Surveys. 1 Although the prevalence of hypertension is not declining in recent years, hypertension-related mortalities are decreasing. In Taiwan, cardiovascular diseases were the second leading cause of death in 2018 with a mortality rate of 165.8 per 100 000, consisting of a mortality rate of 48.8, 26.1, and 12.8 per 100 000 for heart diseases, cerebrovascular diseases, and hypertension, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The “perfect 24‐hour BP control” strategy taking Asian characteristics into account is essential for achievement of the “zero” cardiovascular event goal . Considerable work has already been done on the journey to achieving this goal . Practically, a staged approach to the 24‐hour management of hypertension should be considered, first targeting morning hypertension, then nocturnal hypertension, followed by daytime hypertension .…”
Section: Perspectivesmentioning
confidence: 99%